Outcomes of Operatively Treated Jones Fractures in Major League Soccer Athletes. Issue 7 (31st July 2020) - Miranda, Alejandro; Gerhardt, Michael; Mandelbaum, Bert; Stone, Jonathan
Objectives: Proximal 5th metatarsal fractures in athletes are common and have been studied in NCAA athletics as well as professional basketball (NBA), football (NFL), and European soccer (UEFA). Given that Jones fractures have not been studied in Major League Soccer (MLS), we sought to: (1) quantify the burden of fractures, (2) compare outcomes, re-fracture rates, and complication rates with other professional sports, (3) analyze factors for treatment failure, and (4) report return to play characteristics. Methods: A HealtheAthlete (Cerner Corporation, North Kansas City, MO) database was used to catalog all MLS injuries including and after the 2012 season. We extracted all possible Jones fracture injuries from these data from the 2013 to 2017 seasons (January 1, 2013 through December 31, 2017) using key words "toe, " "Jones, " "metatarsal, " "fracture, " and "fifth." Over 12, 000 unique injuries were cataloged; 141 were initially further investigated. Eighty-four were deemed benign, leaving 57 injuries; 12 were reported twice and 3 had 2 different dates of injury, leaving 42 injuries. We then contacted each team chief medical officer for more information including: demographics, date and mechanism of injury, injury classification (zone), prior or contralateral injury, limb dominance, imaging, operative vs. non-operative treatment, details regarding operative treatment if relevant, time to radiographic healing, time to return to sport, and complications including known re-fracture. Twenty-one injuries were further excluded, leaving 21 operatively treated Jones fractures in 18 players. Results: We analyzed 21 operatively treated Jones fractures in 18 players over the five-year study period. Fracture incidence was 0.37 ± 0.08 fractures per 1000 game exposure hours, or 0.063 ± 0.014 fractures per 1000 total exposure hours. Average age, weight, height, and BMI of players at time of fracture was 25.0 ± 3.7 years, 171.3 ± 17.2 lbs, 70.6 ± 3.2 inches, and 24.2 ± 1.9, respectively. 73.7% of players were right foot dominant, and 52.4% of players had right-sided injuries; 1 player reported bilateral injuries. Player position was reported as predominantly defense, midfield, or forward 44.4%, 16.7%, and 28.9%, respectively. 38.1% of injuries occurred in pre-season, with 38.1% associated with chronic, worsening pain, 23.8% with a rolled ankle/foot, 23.8% with a traumatic event, and 14.3% with a quick cut or pivot. One player reported concomitant medial sesamoiditis, otherwise there were no reported associated injuries. Five (24%) reported a prior contralateral fracture. Two (10%) reported a prior ipsilateral non-operatively treated stress fracture. Zone 2 injuries represented 81% of fractures, with the rest classified as zone 3. Average time into MLS career was 2.6 seasons; 8 (38%) occurred in the rookie season. Re-fracture rate was 4/18 players (22.2%), with 1 player's initial fracture outside the study period; 2 players re-fracture occurred within the study period; and 1 player sustained a re-fracture while on loan (primary fracture included in the study). Average time to re-fracture was 390 days. Treatment for primary fractures (n = 18) included solid screw fixation in 11, cannulated screw fixation in 3, headless cannulated screw fixation in 3, and plate fixation with bone autograft in 1. Treatment for re-fractures (n = 3) included screw exchange with BMAC for 1, screw exchange and bone scaffold with PDGF in 1, and BMAC injection alone with bone stimulator for 1. Average time to radiographic union was 8.3 weeks. Average time to return to play was 10.4 weeks with one outlier removed. Complications include 4 re-fractures, 1 player with screw irritation who required exchange to headless screw with BMAC at 4 months post-op before return to play, 1 mild soft tissue irritation, and 1 mild persistent drainage that resolved with antibiotics. Overall, 20/21 (95%) of players returned to play. Currently, 5 players are retired, 7 remain in MLS, and 6 play in other worldwide professional leagues. Retired players averaged 2.8 years of play after injury. Player return to play characteristics were examined, including games played, games started, full games played, and minutes played; no statistical differences were found. Conclusion: Incidence of Jones fractures appears to be about 1.7x higher than previously reported in European professional soccer (UEFA) (Ekstrand and van Dijk Br J Sports Med 2013). However, articles examining Jones fractures incidence in NFL have shown increased prevalence in the NFL combine over the past few decades (Low et al J Surg Orth Adv 2004, Tu et al FAI 2018, Spang et al OJSM 2018). A significant number of injuries occur in pre-season (38%) and in players' rookie seasons (38%), with the majority playing non-midfield positions. Return to play of 95% and re-fracture rate of 22% are comparable to rates in other professional sports. There does not appear to be any detrimental effect on players' ability to perform after Jones fracture fixation.